Xanthogranulomatous Inflammation of Colon: A Case Report - Ramya Lakshminarayanan; Priyathersini Nagarajan; Divya Madhala; N Nitesh (Journal of Clinical and Diagnostic Research)
Xanthogranulomatous Inflammation (XGI) is a rare pathological condition that can affect various organs, such as lungs, endometrium, vagina, fallopian tube, ovary, testis, stomach, colon, appendix and pancreas. However, most common sites being kidney and gallbladder. XGI has been infrequently documented in the colon, particularly with stricture formation. The current case reports presents the case of a 54-year-old female admitted with a 20 day history of abdominal pain, who was clinically diagnosed with an inflammatory lesion causing luminal narrowing. Colonoscopy revealed a sigmoid polyp, which, upon biopsy, showed acute inflammatory granulation tissue with ulceration. A sigmoidectomy was performed due to persistent pain, revealing a sigmoid colon stricture characterised microscopically by foamy histiocytes amidst dense inflammatory infiltrate and multinucleate giant cell. The present case underscores the importance of considering XGI in patients presenting with bowel mass, obstruction, or stricture.